ANALISIS PENGARUH KEPUASAN KERJA, GAJI DAN IKLIM ORGANISASI TERHADAP PERPINDAHAN KERJA KARYAWAN KONTRAK - Erni Widajanti, Shandy Agita Yoga Kusuma (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2014)
The purpose of this research was to analyze the significance of the influence of job satisfaction, organizational climate on salaries and transfer of employees (employee turnover) on contract employees in the Bank BRI in Sragen. Population of the study was a contract employee at the BRI in Sragen who have worked more than 1 year, amounting to 57 people. The samples in this study were 57 contract employees at Bank BRI in Sragen by using total sampling as a sampling technique. Analytical methods used to test the hypotheses is multiple linear regression analysis with first tested the classical assumptions. Results reveal that H1 is accepted, which means that job satisfaction significantly influence employee transfer contract with Bank BRI in Sragen. H2 is accepted, which means that a significant effect on the movement of wages of employees working on the contract in Sragen BRI. H3 is accepted, which means that the organizational climate significantly influence employee transfer contract with Bank BRI in Sragen. F test results model fit to analyze this research. Regression results obtained values for variables regression coefficient salary of 0,313; in which the value of the regression coefficient is greater than the value of the regression coefficients of other variables, so H4 is accepted, mean wages are the dominant factors that influence the movement of the employee contract with Bank BRI in Sragen. Keywords: job satisfaction, salary, organizational climate, employee displacement.